Clinical practice guidelines in pediatric anesthesia: What constitutes high‐quality guidance?. Issue 2 (27th January 2020) - Olweny, Catherine N.; Arnold, Philip
Abstract: The explosion of scientific evidence has outstripped the ability of individual clinicians to acquire, process, and apply it within a clinical context. Clinical practice guidelines bridge the gap between this large body of evidence and clinical practice by translating evidence into recommendations. As such, they are an important extension of the evidence‐based medicine paradigm. Guidelines promise to translate evidence into actionable clinical recommendations. However, this promise can only be realized if they are both useful and trustworthy. As the number of guidelines increases users' question their role, the quality of the scientific evidence behind them and the strength of the recommendations made. In this article, we provide definitions and outline the features of the common forms of clinical guidance. We then describe the essential characteristics of good quality clinical guidance and outline initiatives aimed at improving quality. Specific issues and limitations related to guideline development in perioperative care of children are discussed. Finally, two clinical guidance documents, published recently in Pediatric Anesthesia, are discussed based upon these criteria.